Sustainability Of Indonesia Smart Card Implementation Continuity According To Perceptions And Opinions In Indonesian Community - Susdarwono, Endro Tri (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The Smart Indonesia Card Policy is a government program launched to address the interrelated problems of poverty and education. This study aims to provide a description regarding the continuity of the implementation of the smart Indonesian card according to perceptions and opinions among Indonesian people. The research approach used is a quantitative approach. The research sample used was 100 respondents located in Malang-Petanglong using a questionnaire instrument. The sampling technique used random sampling. Data analysis used hypothesis testing on signs, and hypothesis testing through the chi-Square distribution. Based on testing the hypothesis on signs, this study concludes that the implementation of KIP continuity needs to be continued. Meanwhile, based on testing the hypothesis through the chi-square distribution, it was concluded that the number of respondents asking for KIP to be discontinued was not constant and therefore a significant factor. Government, it is hoped that the mechanism that changes in each period is followed by clear socialization so that all parties can implement it according to the provisions. In addition, the government should form a Smart Indonesia Card (KIP) monitoring team.